2020
DOI: 10.1088/1757-899x/823/1/012037
|View full text |Cite
|
Sign up to set email alerts
|

Identification of plants natural dye by Meto tribe in South Central Timor

Abstract: Information on plant species, natural dyes and the dying process of the yarn of ikat weaving in South Central Timor is still minimal and not well documented. Therefore, this study aimed to identify natural dye in South Central Timor. The samples were collected by exploration methods. Parts of plants, dyeing processes, and kinds of color were recorded based on observation, interviews with craftsmen and documentation. Our results showed that there are 7 plant species were successfully identified, Curcuma longa L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…Information on the species diversity of these plants have been reported from the areas around community settlements, as their use for coloring woven fabrics by the local community. That earlier study showed that there were dozens of natural dye plants used by artisans from East Nusa Tenggara, such as tarum, turmeric, noni, along with color enhancers such as loba and biduri (Sabuna et al, 2018;Sabuna & Nomleni, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Information on the species diversity of these plants have been reported from the areas around community settlements, as their use for coloring woven fabrics by the local community. That earlier study showed that there were dozens of natural dye plants used by artisans from East Nusa Tenggara, such as tarum, turmeric, noni, along with color enhancers such as loba and biduri (Sabuna et al, 2018;Sabuna & Nomleni, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Kain tenun ini secara tradisional dibuat dengan bantuan masyarakat lokal dan merupakan bagian dari kehidupan sehari-hari Masyarakat (Leki dkk., 2023). Dalam proses pembuatan bahan tenun, masyarakat membutuhkan pewarna yang dapat memberikan corak dan motif pada bahan (Sabuna dan Nomleni 2020). Beberapa tumbuhan pewarna yang digunakan oleh masyarakat lokal secara umum telah dikenal namun terdapat beberapa jenis yang belum dikenal dikarenakan belum terlihat pemanfataannya.…”
unclassified